2017
DOI: 10.1002/mp.12725
|View full text |Cite
|
Sign up to set email alerts
|

Measured and Monte Carlo simulated surface dose reduction for superficial X‐rays incident on tissue with underlying air or bone

Abstract: This work demonstrates the feasibility of using an Advanced Markus chamber with entrance window facing downstream to investigate surface dose reduction with underlying air or bone in tissue. As the field size decreases and beam quality increases surface dose with underlying bone tends to full backscatter values even though tissue thicknesses are below those normally associated with full backscatter. Conversely with underlying bone close to the surface dose will increasingly fall below full backscatter values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was previously shown that surface dose is reduced by up to 12.5% with the presence of underlying bone or 10.5% with shielding material such as lead. 2 , 3 , 4 , 5 , 6 , 7 , 8 There are also significant absorbed dose differences between different tissue types due to the differences in mass energy absorption coefficients. 9 , 10 , 11 Second, the use of an inverse square law correction, or similar, for an average source‐to‐surface distance in the treatment field is a crude mechanism in dealing with highly irregular surfaces present in the head and neck region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that surface dose is reduced by up to 12.5% with the presence of underlying bone or 10.5% with shielding material such as lead. 2 , 3 , 4 , 5 , 6 , 7 , 8 There are also significant absorbed dose differences between different tissue types due to the differences in mass energy absorption coefficients. 9 , 10 , 11 Second, the use of an inverse square law correction, or similar, for an average source‐to‐surface distance in the treatment field is a crude mechanism in dealing with highly irregular surfaces present in the head and neck region.…”
Section: Introductionmentioning
confidence: 99%
“…First, it does not account for the presence of tissue inhomogeneity under skin surface in the region of clinical interest. It was previously shown that surface dose is reduced by up to 12.5% with the presence of underlying bone or 10.5% with shielding material such as lead 2–8 . There are also significant absorbed dose differences between different tissue types due to the differences in mass energy absorption coefficients 9–11 .…”
Section: Introductionmentioning
confidence: 99%